Teks Mitos Ida Ki Dukuh Sakti di Pura Gelar Desa Pakraman Gelogor Kecamatan Ubud Kabupaten Gianyar Analisis: Struktur, Fungsi, dan Nilai - Adidi Saputra, Kadek; Suryati, Ni Made; Mulyawati, Tjok Istri Agung (Humanis, 2018)
The study is titled "The Text of Myth Ida Ki Dukuh Sakti in Gelar temple Pakraman Gelogor village, Ubud District, Gianyar Regency; Analysis of Structure, Function, and Value”. This study aims to describe the structure of the content contained in the mythical text of Ida Ki Dukuh Sakti and to analyze the function and value. The theory used in this research is structural theory, function theory, and value theory. Phase of data provision used method of recall and technique of record. It also used interview method assisted by recording technique and record technique. In the data analysis presentation stage, informal methods are used. The content structure that built the mythical text of Ida Ki Dukuh Sakti there are three, namely opening, content, and cover. In the opening section describes the figure of Ida Ki Dukuh Sakti. In the contents describe the ceremony, sraddha as a form of bhakti, and the disaster that occurred in the village of Pakraman Gelogor. In the closing section describes the end of the mythical text of Ida Ki Dukuh Sakti. The functions contained in the mythical text of Ida Ki Dukuh Sakti, namely (1) social function, (2) function as harmony of natural element, and (3) religious function; while the values ??contained in the mythical text of Ida Ki Dukuh Sakti are (1) magical values ??and (2) the value of local wisdom.